Highlights of the Fourth Canadian Symposium on Hepatitis C: Moving towards a National Action Plan - Selena M. Sagan; Benoit Dupont; Jason Grebely; Mel Krajden; Sonya A. MacParland; Jennifer F. Raven; Sahar Saeed; Jordan J. Feld; D. Lorne Tyrrell; Joyce A. Wilson (Canadian Journal of Gastroenterology and Hepatology)
Hepatitis C virus (HCV) affects at least 268,000 Canadians and causes greater disease burden than any other infectious disease in the country. The Canadian Institutes of Health Research (CIHR) and the Public Health Agency of Canada (PHAC) have identified HCV-related liver disease as a priority. In 2015, the release of well-tolerated, short course treatments (~12 weeks) able to cure the majority of treated HCV patients revolutionized HCV therapy. However, treatment is extremely costly and puts a significant burden on the Canadian healthcare system. Thus, managing treatment costs and improving treatment engagement in those most in need will be a key challenge. Diagnosis and treatment uptake are currently poor in Canada due to financial, geographical, cultural, and social barriers. The United States, Australia, and Scotland all have National Action Plans to prevent, diagnose, and treat HCV in order to efficiently reduce the burden and costs associated with HCV-related liver disease. The theme of the 4th annual symposium held on Feb 27, 2015, “Strategies to Manage HCV Infection in Canada: Moving towards a National Action Plan,” was aimed at identifying strategies to maximize the impact of highly effective therapies to reduce HCV disease burden and ultimately eliminate HCV in Canada.